Aulas práticas no ensino médio: desafios no ensino de biologia em uma escola do interior - Amazonas - Wadick, Eugenio Vargas (Brasil, 2024)
This work aimed to research practical classes in high school, highlighting the challenges in Teaching Biology in a School in the Interior of Amazonas. Practical classes not only complement theoretical teaching, but also play an essential role in building skills, consolidating knowledge and preparing individuals for real-world challenges. The research was carried out with the support of the Federal University of Amazonas, INC campus and by the coordination of the Bachelor of Science course: Biology and Chemistry, Benjamin Constant – AM. This research was carried out at the Pio Veiga state school in the municipality of Atalaia do Norte - Amazonas, in which interviews were carried out with professionals who work daily in different sectors of the school to investigate the challenges of using practical classes in high school specifically in the discipline of Biology. Acting as a teacher is a challenging task, driving strategies and actions that mobilize technical dimensions of being a teacher, but also of affection. Soon after, the semi-structured interview was carried out with 6 questions for management, 10 questions for teachers and 10 for students. It was found in this research that the difficulties faced by the school and teachers are predominant in terms of infrastructure and laboratory materials to teach practical classes. Thus, it can be concluded that the use of practical classes in high school specifically in the Biology discipline is significant for the development of students at the Pio Veiga state school, as it is aligned with the process of building knowledge and learning, creating teaching opportunities and quality education.